2018
DOI: 10.1007/s10865-018-9915-x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity after commitment lotteries: examining long-term results in a cluster randomized trial

Abstract: To overcome self-control difficulties, people can commit to their health goals by voluntarily accepting deadlines with consequences. In a commitment lottery, the winners are drawn from all participants, but can only claim their prize if they also attained their gym-attendance goals. In a 52-week, three-arm trial across six company gyms, we tested if commitment lotteries with behavioral economic underpinnings would promote physical activity among overweight adults. In previous work, we presented an effective 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…From this study, it is found that (variable) monetary incentives can foster health behavior, which is in line with findings from earlier studies [7,8,10,11,13]. However, as opposed to findings from Berardi and colleagues [13], no single reinforcement schedule was found to have a more profound impact on app engagement or the adoption of health behaviors in our study: In our study, every reinforcement schedule we evaluated had a similar impact on user engagement levels.…”
Section: Evaluation Outcomessupporting
confidence: 91%
See 1 more Smart Citation
“…From this study, it is found that (variable) monetary incentives can foster health behavior, which is in line with findings from earlier studies [7,8,10,11,13]. However, as opposed to findings from Berardi and colleagues [13], no single reinforcement schedule was found to have a more profound impact on app engagement or the adoption of health behaviors in our study: In our study, every reinforcement schedule we evaluated had a similar impact on user engagement levels.…”
Section: Evaluation Outcomessupporting
confidence: 91%
“…For example, a study (N = 1299) even found that, to promote the completion of a health risk assessment, it is more effective to distribute financial incentives through a lottery (i.e., prize value of USD 100, with an expected value of USD 25), than to pay end users a fixed fee of USD 25 for completing the assessment [10]. Furthermore, it was found that financial rewards (i.e., EUR 100, or a voucher for a luxury family-vacation) distributed through lotteries are especially promising to increase physical activity levels and gym attendance in overweight adults (N = 163) [11]. Nevertheless, the relationship between different reinforcement schedules and their implications for the overall mHealth campaign costs remain unclear.…”
Section: Introduction 1research Contextmentioning
confidence: 99%
“…A special category of financial exergames are those that employ deposit contracts. To boost one's self-discipline, one may commit to goals by voluntarily accepting deadlines with consequences [57]. Deposit contracts are pre-commitment strategies that force one's future self to certain behaviors [60].…”
Section: Deposit Contracts and Physical Activity Motivationmentioning
confidence: 99%
“…A promising design used by behavioral economists and medical professionals is the use of regret lotteries , which have been demonstrated to support weight loss [ 27 ], medication adherence [ 28 ] and physical activity [ 29 , 30 ] at relatively low costs [ 31 ] across differing populations [ 32 ]. By their design, the lotteries aim to tap into multiple psychological insights on decision-making, with the goal to gain as much health out of every euro spent.…”
Section: Introductionmentioning
confidence: 99%